Safety of Prolonged Wait Time for Nephrectomy for Clinically Localized Renal Cell Carcinoma - Qi, Nienie; Zhao, Fangzheng; Liu, Xiaoxiao; Wei, Wei; Wang, Junqi (Frontiers in Oncology, 2021)
Background There is usually a surgical wait time before nephrectomy for patients with clinically localized renal cell carcinoma, and many factors can influence this preoperative wait time. A relatively prolonged wait time may cause tumor progression. Therefore, we assessed the effect of preoperative wait time on the prognosis of patients with clinically localized renal cell carcinoma. Methods The outcomes of 561 patients with clinically localized renal cell carcinoma who underwent nephrectomy between July 2011 and March 2017 were retrospectively evaluated. According to the wait time before surgery, we divided the patients into three groups: short-wait group (≤ 30 days), intermediate-wait group (> 30 and ≤ 90 days), and long-wait group (>90 days). The clinicopathological characteristics were evaluated, and the survival rates of the three groups were compared. Results This study included 370 male (66%) and 191(34%) female patients, with a median age of 64 years. There were 520 patients with stage T1 and 41 patients with stage T2 tumors. The median interval between diagnosis and surgery was 21 days. There were no significant differences in age, sex, Eastern Cooperative Oncology Group (ECOG) performance status, body mass index, tumor size, surgical approach, surgical procedure, pathological subtype, tumor stage, tumor grade, and residual tumor among the three groups. Overall survival(OS) and cancer-specific survival (CSS) were comparable; the 5-year OS of the short-, intermediate-, and long-wait time groups were 84.2%, 82.0%, and 89.8%, respectively (P=0.732). The 5-year CSS rates of the short-, intermediate-, and long-wait time groups were 87.1%, 88.9%, and 90.4%, respectively (P=0.896). Multivariate analysis revealed that wait time was not an independent prognostic factor for OS or CSS. Conclusion Prolonged surgical wait time (> 90 days) does not influence survival in patients with clinically localized renal cell carcinoma.